Optimalisasi Kompetensi Mahasiswa dalam Melakukan Self-Management Dismenorea Primer melalui Implementasi Evidence Based Nursing Berbasis Intervensi Komplementer - A. Sri Ulfi Nofriati; Megawati Sibulo (Jurnal Pengabdian Masyarakat Nusantara, 2026)
Primary dysmenorrhea is one of the most common reproductive health problems experienced by female university students and may adversely affect academic performance and quality of life. Students' competence in performing self-management of dysmenorrhea through evidence-based non-pharmacological interventions still needs to be strengthened to enable them to manage menstrual pain independently and to prepare them for their future roles as healthcare professionals. This community service program aimed to evaluate the effectiveness of implementing Evidence-Based Nursing through abdominal effleurage massage and acupressure in optimizing students' competence in the self-management of primary dysmenorrhea. The participants were second-year students of the Diploma III Nursing Study Program at Institut Batari Toja Bone who experienced primary dysmenorrhea and were selected using a purposive sampling technique. Data were collected using the Visual Analog Scale (VAS) to assess pain intensity and a competency checklist to evaluate students' practical skills. The expected outcomes of this program were improved student competence in the self-management of primary dysmenorrhea and reduced pain intensity following the application of abdominal effleurage massage and acupressure. This community service program is expected to provide a foundation for the development of complementary nursing education based on Evidence-Based Nursing.